1987
DOI: 10.1021/bi00397a007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of functional group changes in the EcoRI recognition site on the cleavage reaction catalyzed by the endonuclease

Abstract: Oligodeoxynucleotides have been prepared that contain changes in the functional group pattern present in the EcoRI recognition site. These changes involve "functional group deletions", "functional group reversals", and "displaced functional groups". Steady-state kinetic parameters have been used to characterize the interaction of these modified recognition sites with the EcoRI endonuclease. Changes in the functional group pattern have varying effects upon the cleavage reaction. Both the exocyclic amino groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
117
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(126 citation statements)
references
References 63 publications
7
117
1
Order By: Relevance
“…From a linear regression of initial slopes at different substrate concentrations, it was confirmed that EcoRI catalysis obeys the Michaelis-Menten equation (Fig. 5), as already shown by others (30)(31)(32)(33). From an Eadie-Hofstee plot (Fig.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…From a linear regression of initial slopes at different substrate concentrations, it was confirmed that EcoRI catalysis obeys the Michaelis-Menten equation (Fig. 5), as already shown by others (30)(31)(32)(33). From an Eadie-Hofstee plot (Fig.…”
Section: Resultssupporting
confidence: 82%
“…5 Inset) a K M of 14 Ϯ 1 nM was derived. As pointed out by McLaughlin et al (31) the K M value of EcoRI depends sensitively on the size of the substrate. Although most studies cannot be compared due to varying detection methods and reaction conditions (temperature, ionic strength, etc.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…2-AP can substitute for adenine and pair with thymine without changing much of the physicochemical properties of double-stranded polynucleotide (22)(23)(24)(25)(26). 2-AP acts as an adenine and pairs with thymine when present in the template strand during polynucleotide synthesis by DNA polymerase (see the experiments mentioned in the Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The self-complementary oligomer d(CTGAnPTTCAG)2 was prepared as described (McLaughlin et al, 1988) using the segmental solid-phase phosphotriester method. Stock solutions were made up in distilled water.…”
Section: Materlals and Methodsmentioning
confidence: 99%